Bahasa Melayu Riau : sumbangan bahasa Melayu Riau kepada bahasa dan bangsa Indonesia - Hamidy, U. U., 1943- (Badan Pembina Kesenian Daerah Propinsi Riau, 1973)
Malay language spoken in the Riau Islands and its relation to the development of Indonesian as a national language.